A Community at Work for Good: The Role OCBs and Interconnectedness Play in Mitigating Workplace Deviance - Moore, Tom; McTier, William; Blevins, Kassie (Archives of Business Research, 2021)
The current research examines the role interconnectedness, a major construct of workplace spirituality, plays in the functioning of workplace deviance behaviors and organizational citizenship behaviors (OCBs) in organizations. The dichotomy between workplace deviance and OCBs can be viewed as a continuum that varies in every organization, but the desire to improve the continuum’s balance remains a constant. Thus, how can the balance of these behaviors be guided towards OCBs and away from workplace deviance simultaneously? Rarely have suggestions been offered by management scholars on how to increase OCBs and reduce workplace deviance simultaneously. Previous recommendations on reducing workplace deviance have focused mostly on costly and inefficient activities, resulting in an increase in more diverse negative deviant behaviors. Thus, what can an organization do to positively change these behaviors in a low realized cost fashion that otherwise does not promote other negative deviant behaviors? An extensive literature search was performed, and no previous scholarly literature could be found that directly addressed interconnectedness and its relationship with the continuum of OCBs and negative workplace deviant behaviors. As a result, previous scholarly and practitioner literature was used to develop theory delineating the relationships of concern. Formal propositions are developed to describe the relationships of interest. A conceptual partially mediated model illustrating how interconnectedness can impact the OCB and workplace deviance continuum is also proposed. Organizational implications are also discussed.